Program Penguatan Karakter Melalui Modul Proyek Bangunlah Jiwa dan Raganya Terhadap Perilaku Siswa Anti-Bullying di SMP Swasta Methodist 7 Medan - Anjelina Pasaribu; Jamaludin Jamaludin; Abdinur Batubara; Surya Dharma; Sampitmo Habeahan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the effectiveness of the character-strengthening program through the “Bangunlah Jiwa dan Raganya” project module in shaping anti-bullying behavior among students at Methodist 7 Private Junior High School, Medan. The main focus of this research is to determine the extent of students’ understanding of the values embedded in the Pancasila Student Profile Strengthening Project (P5) within the context of anti-bullying, as well as to evaluate the effectiveness of the program in changing students’ attitudes toward bullying behavior. This research employs a qualitative approach with a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing or verification. The findings reveal that the P5 program, through the “Bangunlah Jiwa dan Raganya” project module, has proven effective in fostering students’ empathetic, caring, and courageous behavior in rejecting bullying. Students’ understanding of the project theme also improved, particularly in balancing physical and mental aspects. Teachers play a crucial role as facilitators, role models, and motivators, although challenges remain in terms of limited student motivation and lack of parental support. Therefore, this program makes a significant contribution to bullying prevention efforts in schools.